2015
DOI: 10.1017/s0007114515001646
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia prevalence may be reduced among countries that fortify flour

Abstract: The effectiveness of flour fortification in reducing anaemia prevalence is equivocal. The goal was to utilise the existing national-level data to assess whether anaemia in non-pregnant women was reduced after countries began fortifying wheat flour, alone or in combination with maize flour, with at least Fe, folic acid, vitamin A or vitamin B 12 . Nationally representative anaemia data were identified through Demographic and Health Survey reports, the WHO Vitamin and Mineral Nutrition Information System databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…However, it should be noted that they cannot prevent or treat anaemia caused by infections and inflammation, which are common in tropical countries. As the fortification countries evaluated by Barkley et al (3) mostly conformed to the WHO recommendations on Fe fortification of flour, the study confirms that if these WHO recommendations are followed, the prevalence of IDA can decrease. However, as most of the other eighty countries that fortified flour did not follow the WHO recommendations, many of these national flour fortification programmes would be expected to have little or no effect on the Fe status or IDA prevalence in their populations.…”
supporting
confidence: 65%
“…However, it should be noted that they cannot prevent or treat anaemia caused by infections and inflammation, which are common in tropical countries. As the fortification countries evaluated by Barkley et al (3) mostly conformed to the WHO recommendations on Fe fortification of flour, the study confirms that if these WHO recommendations are followed, the prevalence of IDA can decrease. However, as most of the other eighty countries that fortified flour did not follow the WHO recommendations, many of these national flour fortification programmes would be expected to have little or no effect on the Fe status or IDA prevalence in their populations.…”
supporting
confidence: 65%
“…In the 12 countries that had fortified, there was a 2.4% reduction in the odds of anemia prevalence, in comparison with no reduction in the odds of anemia prevalence in 20 countries that never fortified flour. 43 In several Latin American countries, vitamin A-fortified sugar has been effective in reducing vitamin A deficiencies. 44 In Guatemala, where the technology for fortifying sugar with vitamin A was developed, an evaluation of the fortification program carried out showed that after 12 months of implementation, low retinol levels had decreased to 5% and prevalence of human milk samples with less than 20-mg retinol/dL was reduced by 50%.…”
Section: Effectiveness Of Food Fortificationmentioning
confidence: 99%
“…Fortification of wheat flour with iron and other micronutrientswhich include zinc, folic acid, and B vitamins-is mandatory in 81 countries, some of which also require fortification of maize flour. Although Pachon et al (2015) found limited effectiveness of flour fortification reducing prevalence of anemia in women, another review found that countries that fortify wheat flour at WHO guideline levels, after controlling for the level of development as measured by the Human Development Index and for malaria prevalence, yield a 2.4 percent reduction in the odds of anemia in nonpregnant women per year compared with countries that do not fortify (Barkley, Wheeler, and Pachon 2015). Therefore fortification can prove beneficial for large-scale reduction in anemia in general populations, and particularly among nonpregnant women.…”
Section: Food-based Interventionsmentioning
confidence: 99%
“…A review of wheat flour fortification programs by Barkley, Wheeler, and Pachon (2015) Daily iron and folic acid supplementation for nonpregnant women is recommended by the WHO for countries where the prevalence of anemia is greater than 40 percent. For the large population of nonpregnant women, weekly iron and folic acid supplementation is included in the analyses because of the greater feasibility of delivering a weekly supplement than a daily supplement.…”
Section: For the General Populationmentioning
confidence: 99%